2022
DOI: 10.1002/pls2.10066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of expanded glass particle size on compressive properties of vinyl ester syntactic foams

Abstract: The most common fillers for syntactic foam development are glass microballoons or fly ash cenospheres. However, the need for improved properties and reduced cost requires exploring other possibilities. In this work, syntactic foams of vinyl ester resin reinforced with expanded glass particles (EG) were fabricated and compressive properties of the composites were studied. The foam EGS was reinforced with smaller particles of size 0.04–0.125 mm in 15, 30, and 45 vol.% and EGL had larger particles of size 0.25–0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…From the calculated theoretical and experimental densities, it is observed that the experimental density is lower than the theoretical density values. This could be attributed to the presence of voids in the composite material during the preparation process of the samples 64 . Void volumes were also calculated and recorded in Table 5 for the six ratios of the composite material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the calculated theoretical and experimental densities, it is observed that the experimental density is lower than the theoretical density values. This could be attributed to the presence of voids in the composite material during the preparation process of the samples 64 . Void volumes were also calculated and recorded in Table 5 for the six ratios of the composite material.…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to the presence of voids in the composite material during the preparation process of the samples. 64 Void volumes were also calculated and recorded in Table 5 for the six ratios of the composite material. A higher void volume was observed with an increase in the sand content.…”
Section: Density and Void Volumementioning
confidence: 99%
“…Thermoset matrices outperform thermoplastic matrices in terms of chemical stability, yield strength, durability against thermal fluctuation, and creep resistance. [121,184,185] Typically, the thermoset matrix cures at a lower temperature than that needed to produce thermoplastics. Mostly used thermoset polymer matrices are polyester, urea formaldehyde, epoxy, phenolic, vinyl ester, and polyamide.…”
Section: Thermoset Matrixmentioning
confidence: 99%
“…1 Currently, they are applied to aircraft, spacecraft, and marine structures. [2][3][4] Polymer matrix syntactic foams are an essential component in structural applications, such as underwater vehicle structures, submarine buoyancy modules, aircraft components, and thermoforming plugs. [5][6][7][8][9] Shipbuilding control surfaces such as stern planes, rudders, and fairwater planes are composed of syntactic foam due to their superior hydrodynamic performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1960s, these buoyancy aid materials were developed for deep water applications 1 . Currently, they are applied to aircraft, spacecraft, and marine structures 2–4 . Polymer matrix syntactic foams are an essential component in structural applications, such as underwater vehicle structures, submarine buoyancy modules, aircraft components, and thermoforming plugs 5–9 .…”
Section: Introductionmentioning
confidence: 99%